2020
DOI: 10.14533/jbm.20.17
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HIV-1 Reverse Transcriptase Activity by the Extracts of Indian Plants

Abstract: As the currently available therapies for HIV-1 have high costs and are associated with the appearance of multi-drug resistant HIV-1 strains, the Indian traditional medicine system Ayurveda may provide useful alternatives. In this study, we screened the inhibitory activities of various extracts of five Indian plants for inhibitory effects on HIV-1 reverse transcriptase (RT). Water extracts of the leaves of Argemone mexicana strongly inhibited the DNA polymerase activity of HIV-1 RT, which indicated that they co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Argemone mexicana , a stress-resistant member of the Papaveraceae family of plants, has been reported to possess a wide-range of biological activities, such as antibacterial [ 9 12 ], antifungal [ 13 16 ], antiviral [ 17 19 ], anthelmintic [ 20 – 22 ], antioxidant [ 23 25 ] and cytotoxic/anticancer [ 15 , 26 , 27 ] actions. This plant is native to the West Indies, but today it can also be found in Mexico and throughout the Americas [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Argemone mexicana , a stress-resistant member of the Papaveraceae family of plants, has been reported to possess a wide-range of biological activities, such as antibacterial [ 9 12 ], antifungal [ 13 16 ], antiviral [ 17 19 ], anthelmintic [ 20 – 22 ], antioxidant [ 23 25 ] and cytotoxic/anticancer [ 15 , 26 , 27 ] actions. This plant is native to the West Indies, but today it can also be found in Mexico and throughout the Americas [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have tested the antiviral properties of the extracts of P. hysterophorus , and it was observed that the extract of leaves of the plant prepared in aqueous medium at room temperature exhibited very strong anti-HIV potential with IC 50 value being 0.081 mg/mL followed by the ethyl acetate extract of flower at the high temperature (0.31 mg/mL) in comparison to other extracts of the plant [ 37 ]. In the present study, the order of antiviral activity of other extracts from leaves of plant was as follows: ethyl acetate extract prepared at room temperature (IC 50 -0.34 mg/mL)>extracts prepared at high temperature in aqueous (IC 50 -0.40 mg/mL)>and hexane (IC 50 -0.44 mg/mL).…”
Section: Discussionmentioning
confidence: 99%
“…A. mexicana belongs to the Papaveraceae family, which possesses antibacterial [18][19][20], antifungal [21,22], antiviral [23,24], antioxidant [25,26], and cytotoxic/anticancer [27] properties. The emergence of drug-resistant microbial strains [28] has necessitated the search for antimicrobial compounds from natural sources, such as plants and marine microorganisms.…”
Section: Antimicrobial Activity Of Various a Mexicana Extractsmentioning
confidence: 99%
“…HIV uses reverse transcriptase (RT) to convert its RNA to cDNA. Ishizuka et al, 2020 [23] have shown that RT exhibits RNA-and DNA-dependent DNA polymerase activities and RNase H activity. In the present study, the aqueous extract of leaves prepared at a high temperature indicated the maximum inhibitory activity against HIV-1 RT, much like any other nonnucleoside reverse transcriptase inhibitor (NNRTI), as demonstrated by Sanna et al, 2018 [33].…”
Section: Antimicrobial Activity Of Various a Mexicana Extractsmentioning
confidence: 99%